Qualitative/Quantitative Comparison of Changes in Alanya Rural Architecture in terms of CO2 Emissions and Energy Conservation within the Scope of Sustainability - Ercan Aksoy; Özlem Sağıroğlu Demirci (Iconarp International Journal of Architecture and Planning, 2022)
Due to the rapid growth and development caused mainly by tourism of Alanya, rural areas are affected, losing their original texture and authentic structures and being exposed to unqualified interventions. The aim of this study is to determine the original features and reveal the value of Alanya rural architecture within the framework of the sustainability principles, and to determine how these values have changed with the unqualified interventions, by detailing qualitatively and quantitatively on the basis of each intervention. Within the scope of the study, the rural architectural heritage in Alanya has been documented in terms of settlement texture, space organization, architectural elements, material, construction and energy efficiency. For the analysis, a rural house that preserves its original values was used. A comparison was made between the values of this house and the values obtained as a result of the changes in the other buildings in the area. In cases where these interventions are applied in various variations, the changes in the heating and cooling load of the house are compared with the CO2 emission. It has been determined that the rural houses of Alanya provide energy conservation in a way that is perfected by tradition, both in terms of settlement features and space and materials on the basis of structure. It has been determined that the heating/cooling energy requirement can decrease but the CO2 emission increases in the individual changes made by evaluating different types of deterioration. When the most common application variations detected in the field are evaluated, it has been determined that both the heating/cooling energy requirement and the CO2 emission have increased. Rural settlements and residences define an architecture that has reached the highest level in terms of convenience, functionality and economy. Since any intervention to these structures means the loss of their energy conservation properties as well as their originality, a very careful decision should be made. The study reveals the first data in which the rural architecture of Alanya is evaluated within the scope of sustainability and energy and CO2 emissions are compared depending on deterioration/changes.